Measurement of CP violation in B0 → D*±D∓ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dembiski, H.-P.; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; et al. (Journal of high energy physics, 2020)
The decay-time-dependent CP asymmetry in B0→ D∗±D∓ decays is mea- sured using a data set corresponding to an integrated luminosity of 9 fb−1 recorded by the LHCb detector in proton-proton collisions at centre-of-mass energies of 7, 8 and 13 TeV.
Im Titel sind "0", "±" und "∓" hochgestellt
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, A. Comerma-Montells, P. d’Argent, H.-P. Dembinski, M. Dziewiecki, D. Gerick, J. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, H. Malygina, J. Marks, N. Meinert, S. Neubert, A. Piucci, M. Schmelling, N. Skidmore, S. Stemmle, U. Uwer, H. Viemann, R. Waldi, M. Zavertyaev, A. Zhelezov und weitere 876
Gesehen am 14.04.2021